2023
DOI: 10.21037/tau-23-337
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of pelvic floor muscle training on stress urinary incontinence following prostatectomy: a systematic review and meta-analysis

Liping Xin,
Maomao Li,
Minli Pan

Abstract: Background Prostatectomy often causes urinary incontinence, especially stress Urinary incontinence, which has a serious impact on the quality of life of patients. Previous studies have proved that pelvic floor muscle training can help restore pelvic floor function and reduce Urinary incontinence, but the quantitative evaluation and systematic analysis of its effect have not yet been clear. This meta-analysis aimed to systematically evaluate the therapeutic effect of pelvic floor muscle training on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Similarly, in a systematic review of 886 patients with pelvic floor dysfunction after gynecological cancer concluded that pelvic floor muscle training (PFMT) with yoga or core exercises was 95% beneficial for sexual function and urinary incontinence [56]. In addition, PFMT significantly improved patient-reported stress incontinence from 1 month to 1 year after prostatectomy [57].…”
Section: Urinary Incontinencementioning
confidence: 99%
“…Similarly, in a systematic review of 886 patients with pelvic floor dysfunction after gynecological cancer concluded that pelvic floor muscle training (PFMT) with yoga or core exercises was 95% beneficial for sexual function and urinary incontinence [56]. In addition, PFMT significantly improved patient-reported stress incontinence from 1 month to 1 year after prostatectomy [57].…”
Section: Urinary Incontinencementioning
confidence: 99%